Akdeniz Chemson increases zinc borate capacity. Issue 3 (March 2021) - Unknown
Abstract : Akdeniz Chemson, a global supplier of PVC stabilisers, has launched the first phase of its new plant in Izmir, Turkey, which will produce 3, 000 tonnes of zinc borate annually, making the company a leading manufacturer of flame retardant chemicals.